Organizational Development MSME in Facing Organizational Change at UD. Surya Onix - Thusy Tiara Saraswati; Novita Aprilia (CV Pena Jaya Pers, 2025)
Purpose: This study aims to analyze the application of organizational development in an SME context to respond to continuous organizational change at UD. Surya Onix. Design/methodology/approach: A qualitative case study was employed using interviews, observations, and document analysis to explore organizational development practices and human resource dynamics. Findings: The findings indicate that organizational change is driven by human resource behavior and environmental uncertainty, while organizational development functions as an adaptive, behavior-centered mechanism through process consultation, sensitivity training, and employee development. Research limitations/implications: This study is limited to a single SME case, restricting generalizability to other sectors or organizational contexts. Practical implications: he results provide practical insights for SME owners to manage change through people-centered and flexible organizational development practices. Originality/value: This study contributes by illustrating how organizational development theory is applied informally in resource-constrained SMEs.